Outcome and feasibility of palliative chemotherapy in very elderly patients with metastatic breast cancer. Issue 3 (20th September 2019) - Overgaauw, Audrey J. C.; Speijers‐van der Plas, Linda M.; Hendriks, Mathijs P.; Smorenburg, Carolien H.
Abstract: In the Netherlands, approximately 1300 women aged ≥75 years die every year of metastatic breast cancer (MBC). Data on palliative chemotherapy (CT) in very elderly patients are rare, and prospective studies appeared cumbersome. Therefore, we retrospectively analyzed the outcome and feasibility of chemotherapy in elderly MBC patients. Records of all patients with MBC aged ≥75 years who received first‐line palliative chemotherapy between January 2000 and December 2014 at two large teaching hospitals in the Netherlands were reviewed. We registered patient and tumor characteristics together with data on previous adjuvant treatment, palliative endocrine treatment, comorbidities, clinical benefit (defined as ≥6 months progression‐free survival), toxicity, and the reason for stopping chemotherapy. Patients with progressive disease (PD) or death within 30 days after starting CT were censored from analysis. A total of 54 patients with a median age of 77.6 years (range 75‐90) were treated with palliative chemotherapy for MBC. Of them, 20 patients (37%) were aged ≥ 80 years. There was clinical benefit in 28 patients (52%). Median progression‐free survival and median overall survival were 6.0 and 14.0 months, respectively. One year after the diagnosis of MBC, 27 patients (50%) were still alive and 15 patients (28%) lived longer than 2 years. Reasons for stopping CT were progressive disease (n = 32) or toxicity (n = 13). Most patients (n = 48) died of MBC while two patients died of toxicity. In selected patients with MBC aged 75 years or older, single‐agent palliative chemotherapy is feasible and may have clinical benefit.